Altering the mRNA-1273 dosing interval impacts the kinetics, quality, and magnitude of immune responses in mice - Garcia-Dominguez, Dario; Henry, Carole; Ma, LingZhi; Jani, Hardik; Amato, Nicholas J.; Manning, Taylor; Freyn, Alec; Davis, Heather; Hsiao, Chiaowen Joyce; Li, Mengying; Koch, Hillary; Elbashir, Sayda; et al. (Frontiers in Immunology, 2022)
For a vaccine to achieve durable immunity and optimal efficacy, many require a multi-dose primary vaccination schedule that acts to first “prime” naive immune systems and then “boost” initial immune responses by repeated immunizations (ie, prime-boost regimens). In the context of the global coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 2-dose primary vaccination regimens were often selected with short intervals between doses to provide rapid protection while still inducing robust immunity. However, emerging post-authorization evidence has suggested that longer intervals between doses 1 and 2 for SARS-CoV-2 vaccines may positively impact robustness and durability of immune responses. Here, the dosing interval for mRNA-1273, a messenger RNA based SARS-CoV-2 vaccine administered on a 2-dose primary schedule with 4 weeks between doses, was evaluated in mice by varying the dose interval between 1- and 8-weeks and examining immune responses through 24-weeks after dose 2. A dosing interval of 6 to 8 weeks generated the highest level of antigen-specific serum IgG binding antibody titers. Differences in binding antibody titers between mRNA-1273 1 µg and 10 µg decreased over time for dosing intervals of ≥4 weeks, suggesting a potential dose-sparing effect. Longer intervals (≥4 weeks) also increased antibody-dependent cellular cytotoxicity activity and numbers of antibody secreting cells (including long-lived plasma cells) after the second dose. An interval of 6 to 8 weeks elicited the strongest CD8+ T cell responses, while an interval of 3 weeks elicited the strongest CD4+ T cell response. Overall, these results suggest that in a non-pandemic setting, a longer interval (≥6 weeks) between the doses of the primary series for mRNA-1273 may induce more durable immune responses.